EFFECTS OF KETAMINE ON EXPLICIT AND IMPLICIT SUICIDAL COGNITION: A RANDOMIZED CONTROLLED TRIAL IN TREATMENT‐RESISTANT DEPRESSION. Issue 4 (25th March 2014) - Price, Rebecca B.; Iosifescu, Dan V.; Murrough, James W.; Chang, Lee C.; Al Jurdi, Rayan K.; Iqbal, Syed Z.; Soleimani, Laili; Charney, Dennis S.; Foulkes, Alexandra L.; Mathew, Sanjay J.
<x xml:space="preserve">Abstract</x> Background Preliminary evidence suggests intravenous ketamine has rapid effects on suicidal cognition, making it an attractive candidate for depressed patients at imminent risk of suicide. In the first randomized controlled trial of ketamine using an anesthetic control condition, we tested ketamine's acute effects on explicit suicidal cognition and a performance‐based index of implicit suicidal cognition (Implicit Association Test; IAT) previously linked to suicidal behavior. Method Symptomatic patients with treatment‐resistant unipolar major depression (inadequate response to ≥3 antidepressants) were assessed using a composite index of explicit suicidal ideation (Beck Scale for Suicidal Ideation, Montgomery‐Asberg Rating Scale suicide item, Quick Inventory of Depressive Symptoms suicide item) and the IAT to assess suicidality implicitly. Measures were taken at baseline and 24 hr following a single subanesthetic dose of ketamine (n = 36) or midazolam (n = 21), a psychoactive placebo agent selected for its similar, rapid anesthetic effects. Twenty four hours postinfusion, explicit suicidal cognition was significantly reduced in the ketamine but not the midazolam group. Results Fifty three percent of ketamine‐treated patients scored zero on all three explicit suicide measures at 24 hr, compared with 24% of the midazolam group (χ2 = 4.6; P = .03). Implicit associations between self‐ and escape‐related words were reduced following ketamine (P = .01; d = .58) but not midazolam (P = .68; d = .09). Ketamine‐specific decreases in explicit suicidal cognition were largest in patients with elevated suicidal cognition at baseline, and were mediated by decreases in nonsuicide‐related depressive symptoms. Conclusions Intravenous ketamine produces rapid reductions in suicidal cognition over and above active placebo. Further study is warranted to test ketamine's antisuicidal effects in higher‐risk samples.